2021
DOI: 10.30539/ijvm.v45i2.1259
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hymenolepis spp. in House Mice in Baghdad City, Iraq

Abstract: The prevalence of house mice (Mus musculus) Hymenolepiasis was determined in Baghdad, Iraq to study the effects of location, sex, and months on the infection rate of Hymenolepis spp. in house mice. Fifty house mice were captured from Abu Ghraib and Al-Ameriya, Baghdad, Iraq and examined for detecting parasites in laboratory in College of Veterinary Medicine, University of Baghdad. The total infection prevalence of intestinal parasites was 11 (22%) out of 50 samples, the higher prevalence was 28.57% and found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Recently Majeed and Al-Amery (2021) recorded two species of Hymenolipis in house mice in Baghdad Province, and they revealed that the house mice were infected with Rodentolepis nana 4 (8%) and Hymenolepis diminuta 7 (14%). A previous study in the same area Saida (2016a) recorded Rodentolepis nana in 8 mice (23.5%), and he recorded this parasite in 1.2% of patients admitted to the hospitals of Erbil City.…”
Section: A Survey Of Ecto and Endo-parasitesmentioning
confidence: 99%
“…Recently Majeed and Al-Amery (2021) recorded two species of Hymenolipis in house mice in Baghdad Province, and they revealed that the house mice were infected with Rodentolepis nana 4 (8%) and Hymenolepis diminuta 7 (14%). A previous study in the same area Saida (2016a) recorded Rodentolepis nana in 8 mice (23.5%), and he recorded this parasite in 1.2% of patients admitted to the hospitals of Erbil City.…”
Section: A Survey Of Ecto and Endo-parasitesmentioning
confidence: 99%
“…These investment commissions have main objective is to facilitate the procedures for establishing projects for local and foreign investors through the single investment window system (Majeed, 2022). The major task of this body is to encourage, support, and take care of foreign and local investment through a package of incentives and facilities granted to investment projects, facilitating the issuance of the necessary licenses for projects, and granting tax and customs exemptions under this law (Shubber, 2009).…”
Section: Introductionmentioning
confidence: 99%